High-gain chalcogenide avalanche photodetector and preparation method thereof
By designing an InSe photodetector with a semiconductor stacked structure and utilizing chalcogenide materials with different doping or alloying properties, the problem of the inability to balance the responsiveness and speed of the InSe photodetector was solved, and a high-gain and fast-response photodetection effect was achieved.
Patent Information
- Application Number
- CN202510828962.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-20
- Publication Date
- 2025-10-17
AI Technical Summary
Existing InSe photodetectors cannot achieve both high photosensitivity and fast response speed, especially in heterostructures where the carrier recombination rate is high, resulting in the inability to achieve both response speed and photosensitivity.
It adopts a semiconductor stacked structure design, including an N+-type doped or alloyed charge layer, a P-type doped or alloyed multiplication layer, an i-type light absorption layer and a P+-type doped or alloyed buffer layer. By constructing continuous energy band alignment and carrier concentration difference, an avalanche multiplication zone is formed to achieve rapid carrier separation and multiplication.
A high-gain, fast-response photodetector has been achieved, which is suitable for detecting weak light signals, has improved light responsivity and response speed, and is suitable for detection applications in the visible to near-infrared band.
Smart Images

Figure CN120813073A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of two-dimensional material photoelectric detectors, and particularly relates to a high-gain chalcogenide avalanche photodetector and a preparation method thereof. BACKGROUND
[0002] A photoelectric detector is a device for converting optical signals into electrical signals. In recent years, photoelectric detection technology has developed rapidly and is widely used in optical communication, imaging, environmental monitoring, auxiliary driving, and industrial control. Semiconductor photoelectric detectors have small size, low power consumption, and high energy resolution, wide energy response linear range, and short response time, and gradually become the mainstream technology in the field of photoelectric detection. With the development of integrated circuits, device miniaturization is an inevitable requirement to improve integration and reduce energy consumption.
[0003] Emerging two-dimensional materials have attracted much attention in the field of electronic and optoelectronic devices. Among them, metal chalcogenides (including indium selenide, molybdenum sulfide, gallium selenide, etc.) such as indium selenide (InSe) have strong light-matter interaction, adjustable optical bandgap with thickness, high carrier mobility, and strong light absorption, etc. excellent characteristics, and have ultra-high specific surface area, and have a very broad application prospect in the fields of photoelectric detection, optical communication and optical computing, and are important candidate materials for high-performance photoelectric detectors. However, the current InSe photoelectric detector has the following problems:
[0004] (1) The photoelectric conductive and phototransistor-based detector usually has high light responsivity, but the response speed is slow.
[0005] (2) The photoelectric detector based on planar or vertical structure van der Waals heterojunction has a faster response speed, but has a lower light responsivity, and cannot realize high-sensitivity detection of weak light signals.
[0006] Obviously, the current reported InSe photoelectric detector cannot meet the application requirements of high responsivity and fast response speed. Therefore, it is of great significance to propose a photoelectric detector with high gain and fast response speed and a preparation method thereof.
[0007] Document 1 "Lei S, Ge L, Najmaei S, et al. Evolution of the electronic bandstructure and efficient photo-detection in atomic layers of InSe. ACS Nano, 2014, 8(2): 1263-1272." reports an avalanche photodetector by constructing an InSe-Al Schottky junction, which has a responsivity of 0.1 A / W at 532 nm wavelength and 26.5 mW / cm 2The response time under illumination is 60 μs.
[0008] Document 2“Gao A, Lai J, Wang Y, et al. Observation of ballistic avalanche phenomena in nanoscale vertical InSe / BP heterostructures. Nature Nanotechnology, 2019, 14(3): 217-223.” reports an avalanche photodetector by constructing an InSe-BP vertical heterojunction structure, which has a high optical gain and low noise at a wavelength of 4 μm.
[0009] The above method realizes visible-infrared band light detection for the avalanche photodetector prepared based on the InSe material, has a high optical gain and a fast response time, but the Schottky structure used has a large carrier barrier, and a large reverse bias needs to be used. Meanwhile, in the heterojunction photodetector constructed by two-dimensional materials, a large interface state density is often introduced due to the lattice mismatch, electronegativity difference and interface defect between different materials; these interface states are easy to capture photo-generated carriers, causing serious interfacial layer recombination, so that part of the carriers are lost before being collected, thereby reducing the external quantum efficiency and responsivity of the device. Meanwhile, when there are multiple heterojunction interfaces, the diffusion time of photo-generated carriers is long, and the carriers are recombined in the material, thereby limiting the response speed of the device.
[0010] In view of the above problems, there is an urgent need to develop a photodetector with high responsivity and fast response speed to solve the problem that the existing chalcogenide (InSe) photodetector cannot balance the light responsivity and response speed. SUMMARY
[0011] The purpose of the present application is to solve the problem that the existing chalcogenide (InSe) photodetector cannot balance the light responsivity and response speed, and to provide a high-gain chalcogenide avalanche photodetector and a preparation method thereof.
[0012] In view of the problem that the photoresponsivity and response speed of the existing chalcogenide (InSe) photoelectric detector cannot be considered, the research team of the present application has carried out in-depth research. In the current mainstream photoelectric detector device design, including the common photoconductive detector, PN junction type detector and the detector based on two-dimensional / three-dimensional material heterostructure, all face the universal technical bottleneck that the photoresponsivity and response speed are difficult to consider. It is found that the reason for this phenomenon is that the light absorption thickness is designed to be large in the photoelectric detector to improve the light absorption efficiency, the diffusion time of the photo-generated carrier is long, the carrier is combined in the material, and then the response speed of the device is limited. If the junction thickness or the light absorption layer thickness is reduced to improve the response speed, the light absorption rate will be significantly sacrificed, resulting in a decrease in photoresponsivity. Especially in the heterostructure, the carrier needs to cross multiple heterojunction interfaces to be collected by the electrode, which significantly increases the transmission path and the combination probability of the carrier, causing the problem that the response speed and the photoresponsivity cannot be considered.
[0013] Therefore, the current traditional PN junction and heterostructure photoelectric detector generally faces the problem that the response speed and the photoresponsivity are difficult to consider, and the electric field distribution of the junction is uneven, and the carrier collection efficiency is limited.
[0014] To achieve the above purpose, the technical solution provided by the present application is to stack the chalcogenide (such as InSe) two-dimensional material with different doping or alloying to form an avalanche photoelectric detector with a semiconductor stack structure, realize the rapid separation of the carrier in the absorption zone and the multiplication zone, and improve the photoresponsivity and response speed of the detector, specifically:
[0015] A high-gain chalcogenide avalanche photoelectric detector, characterized in that it comprises a substrate, a dielectric layer (also called an insulating layer, which has a certain shielding effect on the carrier), a semiconductor stack structure, a lower electrode and an upper electrode.
[0016] The dielectric layer is located on the upper surface of the substrate.
[0017] The semiconductor stack structure is located on the upper surface of the dielectric layer, and includes a charge layer, a multiplication layer, a light absorption layer and a buffer layer from bottom to top.
[0018] The charge layer is an N + doped or alloyed chalcogenide two-dimensional material; the multiplication layer is a P +The semiconductor multilayer structure is formed by different doped or alloyed chalcogenide compound two-dimensional materials, and the adjacent two layers are in van der Waals contact through van der Waals force, and the two layers are in close contact and do not fall off, and finally form an avalanche detector based on the combination of intrinsic / doped or alloyed chalcogenide compounds; the photoelectric detector adopts a surface incident mode, that is, the incident direction of the incident light is from the P-type chalcogenide compound two-dimensional material to the i-type chalcogenide compound two-dimensional material to the entire avalanche multiplication region.
[0019] The electron concentration of the charge layer is 5×10 17 -9×10 18 cm -3 -5×10 17 -5×10 18 cm -3 -5×10 16 -5×10 17 cm -3 -9×10 17 -9×10 18 cm -3 ;
[0020] The lower electrode is not in contact with the semiconductor multilayer structure and is located on the upper surface of the dielectric layer.
[0021] The upper electrode is located on the upper surface of the buffer layer and forms an ohmic contact with the buffer layer.
[0022] The above semiconductor multilayer structure is formed by different doped or alloyed chalcogenide compound two-dimensional materials, and the adjacent two layers are in van der Waals contact through van der Waals force, and the two layers are in close contact and do not fall off, and finally form an avalanche detector based on the combination of intrinsic / doped or alloyed chalcogenide compounds; the photoelectric detector adopts a surface incident mode, that is, the incident direction of the incident light is from the P + The semiconductor multilayer structure is formed by different doped or alloyed chalcogenide compound two-dimensional materials, and the adjacent two layers are in van der Waals contact through van der Waals force, and the two layers are in close contact and do not fall off, and finally form an avalanche detector based on the combination of intrinsic / doped or alloyed chalcogenide compounds; the photoelectric detector adopts a surface incident mode, that is, the incident direction of the incident light is from the P
[0023] Further, the thickness of the charge layer is 5-50 nm.
[0024] The thickness of the multiplication layer is 5-80 nm.
[0025] The thickness of the light absorption layer is 10-200 nm.
[0026] The thickness of the buffer layer is 10-100 nm.
[0027] Further, the doping elements in the charge layer are one or more of Ge, Sn, Pb, Cl, Br and I, and the alloying is one or more of InGaSe, InSeTe and InSeS.
[0028] The doping elements in the multiplication layer are one or more of Mn, V, Zn, Cd, Hg, Sb, Al, As and Bi, and the alloying is one or more of InGaSe, InSeTe and InSeS.
[0029] The doping elements in the buffer layer are one or more of Mn, V, Zn, Cd, Hg, Sb, Al, As and Bi, and the alloying is one or more of InGaSe, InSeTe and InSeS.
[0030] Further, the lower electrode comprises a first electrode and a second electrode, which are respectively located on both sides of the upper surface of the dielectric layer, and are made of one or more combinations of Cr, Ti, Ag, Au, Pt, Al, In, Pa, W, graphite, ITO, FTO and AZO, and have a thickness of 10-80 nm.
[0031] The upper electrode comprises a third electrode and a fourth electrode, which are respectively located on the upper surface of the buffer layer and do not contact each other, and are made of one or more combinations of Cr, Ti, Ag, Au, Pt, Al, In, Pa, W, graphite, ITO, FTO and AZO, and have a thickness of 10-80 nm.
[0032] The lower electrode and the upper electrode can each be composed of a single layer or multiple layers of conductive material.
[0033] Further, the substrate is made of one of Si, sapphire, mica, PET, PC and PDMS, and has a thickness of 100-1000 μm.
[0034] The dielectric layer is made of one or more of SiO2, HfO2, Al2O3, hBN and PDMS, and has a thickness of 30-300 nm.
[0035] Further, the chalcogenide compound is InSe, i.e., the prepared detector is an InSe avalanche photodetector.
[0036] Meanwhile, the application provides a preparation method of the high-gain chalcogenide avalanche photodetector, which is characterized by comprising the following steps:
[0037] 1) processing the substrate
[0038] The substrate is treated to remove impurities on the surface of the substrate (including organic matter, inorganic matter, particles and metal ions, etc.), improve the adhesion of the dielectric layer material to the substrate, reduce interface defects and improve device performance stability.
[0039] 2) Preparation of dielectric layer
[0040] One or more of the following methods is used to prepare a dielectric layer on the surface of the substrate treated in step 1): thermal oxidation, chemical vapor deposition, atomic layer deposition, dry transfer, etc.
[0041] Of course, the substrate with a dielectric layer can also be directly purchased from the market to meet the requirements;
[0042] 3) Preparation of lower electrode
[0043] According to the different setting positions of the lower electrode, the lower electrode can be prepared in the following two ways:
[0044] A patterned electrode structure is prepared on the dielectric layer by photolithography process, and an electrode with a thickness meeting the requirements is deposited as the lower electrode by electrode preparation processes such as thermal evaporation, magnetron sputtering and electron beam evaporation;
[0045] Alternatively, a pre-patterned electrode with a thickness meeting the requirements is directly transferred to the surface of the dielectric layer as the lower electrode;
[0046] 4) Preparation of semiconductor stack structure
[0047] 4.1) The doped or alloyed chalcogenide material with the required conductivity type and carrier concentration for the charge layer, multiplication layer, light absorption layer and buffer layer is prepared by melt method (such as vertical Bridgman method and horizontal gradient freezing method);
[0048] 4.2) The chalcogenide material obtained in step 4.1) is prepared into a two-dimensional material meeting the thickness requirements by mechanical exfoliation method one by one in the order of charge layer, multiplication layer, light absorption layer and buffer layer from bottom to top, and is transferred to the target position by dry transfer technology, finally forming a semiconductor stack structure, and the adjacent two layers are not detached from each other;
[0049] 5) Preparation of upper electrode
[0050] 5.1) A patterned electrode is prepared by magnetron sputtering method, electron beam evaporation method or thermal evaporation method combined with a specially designed mask plate;
[0051] 5.2) The upper electrode prepared in step 5.1) (the upper electrode with complete morphology and uniform thickness) is transferred to the upper surface of the buffer layer of the semiconductor stack structure as the upper electrode by dry transfer technology;
[0052] 6) Post-processing
[0053] The device obtained in step 5) is annealed in an inert atmosphere at 100-300° C. for 0.5-5 h to enhance the contact between the two-dimensional materials and between the two-dimensional materials and the electrodes, thereby reducing the contact resistance and ultimately obtaining a chalcogenide avalanche photodetector.
[0054] Furthermore, step 1) is specifically as follows:
[0055] The substrate was immersed in piranha solution (7:3 sulfuric acid and 30% hydrogen peroxide solution) or aqua regia to remove inorganic matter, first rinsed with deionized water, then rinsed in isopropyl alcohol, acetone and ethanol in sequence to remove organic matter, and finally ultrasonically cleaned in deionized water and blown dry with nitrogen.
[0056] Furthermore, step 3) is specifically as follows:
[0057] 3.1) Coating photoresist on the clean dielectric layer surface, applying a mask, curing the photoresist by ultraviolet exposure, and removing the uncured photoresist in a developer to form a patterned electrode structure. In short, this step uses micro-nanofabrication lithography and etching techniques to form the desired pattern corresponding to the first electrode and the pattern corresponding to the second electrode.
[0058] 3.2) Using magnetron sputtering, electron beam evaporation or thermal evaporation to deposit a lower electrode with a thickness that meets the requirements on the exposed electrode structure, and finally using an organic solvent to remove the photoresist on the surface.
[0059] Furthermore, step 4.2) is specifically as follows:
[0060] Use a strong adhesive tape such as Scotch tape or Nitto tape to remove the + The 2D materials are formed by mechanically exfoliating the single crystal of the chalcogenide compound. Then, a plurality of 2D materials are pasted from the tape using a weakly sticky organic substrate such as PDMS, PC or PI. The 2D materials of appropriate size and thickness are selected under a microscope and then transferred to the surface of the dielectric layer as a charge layer by dry transfer technology, ensuring that they do not contact the lower electrode.
[0061] The two-dimensional material is peeled off from the p-type chalcogenide single crystal using the mechanical exfoliation method described above, and the appropriate two-dimensional material is transferred to the surface of the charge layer using the same dry transfer technique as the above method to serve as the multiplication layer;
[0062] The two-dimensional material is formed by mechanically exfoliating the intrinsic chalcogenide single crystal using the above-mentioned mechanical exfoliation method, and the appropriate two-dimensional material is transferred to the surface of the multiplication layer using a dry transfer technique to serve as a light absorption layer;
[0063] The mechanical stripping method described above was used to remove the +Mechanical exfoliation of type chalcogenide compound single crystal to form two-dimensional material, using dry transfer technology to transfer suitable two-dimensional material to the surface of the light absorption layer as a buffer layer;
[0064] The horizontal projection area of the charge layer is greater than the horizontal projection area of the multiplication layer, which is greater than the horizontal projection area of the light absorption layer, which is greater than the horizontal projection area of the buffer layer; the buffer layer currently produced is used as a contact layer of the upper electrode, and too much shielding will affect the number of photons incident on the light absorption layer, so the horizontal projection area of the better buffer layer is smaller than that of the light absorption layer, to ensure a larger effective area of the light absorption layer.
[0065] Further, in step 6), the inert atmosphere is Ar2 or Ar2 / H2 mixture (H2 content ≤5%);
[0066] The annealing temperature is 150°C, and the time is 0.5h.
[0067] The principle of the application is as follows:
[0068] The application improves the light response degree and response speed in the following three aspects:
[0069] The first aspect: based on the avalanche effect of the semiconductor, by designing the structure of the device and the band alignment or carrier concentration difference of the appropriate chalcogenide compound (such as InSe), a photodetector with high gain and promoting photogenerated carrier separation is provided, so as to obtain high light response degree and fast response speed, and has weak light signal detection capability. The device uses a surface incident structure avalanche detector, and the photon absorption and photogeneration process mainly occurs in the i-type semiconductor chalcogenide compound (such as InSe). The nearly uniform electric field in this region separates the electron-hole pairs, so that the electrons and holes drift to the N + region and P + region respectively, when the drifting electrons reach the P region, the electrons are subjected to a larger electric field and obtain more energy to cause collision ionization, a large number of electron-hole pairs are generated, and light gain is generated, thereby improving the light response degree.
[0070] The second aspect: based on the doping or alloying regulation of the chalcogenide compound material (such as InSe), different conductive types and carrier concentrations of the chalcogenide compound material (such as InSe) are obtained, which are used as the charge layer, the multiplication layer, the light absorption layer and the buffer layer respectively. + The P region forms a region with high hole concentration by regulating the doping concentration or component ratio, provides an effective hole injection source, and forms an ohmic contact with the upper electrode; the i region is an intrinsic chalcogenide compound, has a wide depletion width and a low carrier intrinsic concentration, and can support a strong built-in electric field to accelerate the separation process of the photogenerated carriers. After light excitation, electron-hole pairs are generated in the i region, and are rapidly separated under the action of the electric field, and the electrons drift to the N+ Side motion, holes drift to P + Side drift. When the electron drifts to the P region, the electron is affected by a larger electric field to produce collision ionization, and more electron-hole pairs are released in the collision ionization process, that is, an avalanche collision ionization process. The semiconductor stack structure constructed by different chalcogenide compound materials has a continuous energy band alignment, which not only effectively suppresses the energy band bending and barrier problems commonly seen in traditional heterojunctions, but also provides a low-resistance diffusion and drift channel for photo-generated electrons and holes, which is conducive to electron-hole separation / transfer, reduces the recombination of electrons and holes at the junction interface, prolongs the carrier lifetime, and thus improves the light response and response speed of the device.
[0071] Third aspect: the upper electrode covers P + The buffer layer of the chalcogenide compound can regulate the contact characteristics between the metal and the semiconductor, reduce the contact potential barrier and contact resistance of the metal semiconductor, form a carrier transport channel, and improve the light response.
[0072] The advantages of the present application are:
[0073] 1. The present application provides an avalanche photodetector comprising a chalcogenide semiconductor stack structure, which adopts a P + -i-P-N + structure design to introduce an avalanche multiplication design, and by constructing a reasonable energy band alignment structure, a nearly uniform strong electric field is established in the intrinsic chalcogenide compound region, thereby realizing high response to weak light signals. Photo-generated electrons trigger an avalanche collision ionization process under the action of a high electric field, and obtain significant photoelectric gain. Compared with traditional two-dimensional PN-type heterojunction detectors, the present application can realize higher light response and faster response speed, and can be used for detection applications from visible to near-infrared waveband.
[0074] 2. The present application makes full use of the controllability of chalcogenide compound materials (such as InSe), and obtains chalcogenide thin layers with different conductive types and carrier concentrations by alloying or doping, which are respectively used as charge layers, multiplication layers, light absorption layers and buffer layers, to construct a semiconductor stack structure with continuous energy band alignment or different carrier concentrations. This structure helps to reduce interface carrier recombination, prolong the lifetime, improve the separation efficiency, and realize directional design of device structure and response performance, enhance the expandability and tailorability of device function, and the device structure can be extended to other two-dimensional materials.
[0075] 3. The avalanche photodetector of the chalcogenide (such as InSe) stack structure provided by the present application has a simple preparation process, can closely combine semiconductor micro-nano processing technology with two-dimensional material transfer technology, and has strong practicability.
[0076] 4. The semiconductor stack structure in the application forms a high-efficiency avalanche multiplication zone through the control of the thickness and doping concentration of each layer, ensures the carrier transport and multiplication characteristics, and can realize the multiplication and rapid separation of carriers.
[0077] 5. The avalanche photodetector has the advantages of high gain, high responsivity and fast response speed, is suitable for weak light detection, high-sensitivity imaging, biological sensing and the like, and the preparation method is simple and feasible.
[0078] 6. The avalanche photodetector of the InSe stack structure can overcome the problems that the photoconductive type, phototransistor type and heterojunction type photodetectors prepared based on InSe cannot simultaneously achieve high light responsivity and sensitivity (response speed) and have weak response ability to weak signals. BRIEF DESCRIPTION OF DRAWINGS
[0079] Figure 1 is a cross-sectional view of a high-gain InSe avalanche detector;
[0080] Figure 2 is a top view of a high-gain InSe avalanche detector;
[0081] Figure 3 is a schematic diagram of a collision ionization process;
[0082] Figure 4 is the IT characteristic of an InSe avalanche detector under 505 nm light irradiation;
[0083] Figure 5 is the IV characteristic of a symmetric structure device under 505 nm light irradiation;
[0084] Figure 6 is the IT characteristic of a symmetric structure device under 505 nm light irradiation;
[0085] The reference signs are as follows:
[0086] 1-P + buffer layer; 2-i light absorption layer; 3-P multiplication layer; 4-N + charge layer; 5-medium layer; 6-substrate; 7-lower electrode; 8-upper electrode. DETAILED DESCRIPTION
[0087] Preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings. These embodiments are provided to better illustrate the present invention, but are not intended to limit the present invention to these embodiments. Therefore, non-essential improvements and adjustments to the embodiments made by those skilled in the art based on the above-described invention remain within the scope of protection of the present invention.
[0088] The present invention provides a high-gain chalcogenide avalanche photodetector and a preparation method thereof. The specific preparation method is:
[0089] 1) Processing substrate
[0090] The substrate was immersed in piranha solution or aqua regia, first cleaned with deionized water, then cleaned in isopropyl alcohol, acetone and ethanol in sequence, and finally ultrasonically cleaned in deionized water, and the substrate was blown dry with nitrogen.
[0091] 2) Preparation of dielectric layer
[0092] Preparing a dielectric layer on the surface of the substrate treated in step 1);
[0093] 3) Preparation of lower electrode
[0094] The lower electrode is fabricated using common photolithography and etching techniques used in semiconductor micro-nano fabrication. A photoresist is applied to the clean dielectric layer, and a mask is placed on top. The photoresist is cured by ultraviolet exposure, and the uncured photoresist is removed in a developer. The lower electrode is deposited on the dielectric layer using a magnetron sputtering process, and any remaining photoresist is subsequently removed using an organic solvent.
[0095] 4) Preparation of semiconductor stacked structures
[0096] 4.1) Using a melt process to prepare doped or alloyed chalcogenide materials with the required conductivity type and carrier concentration for the charge layer, multiplication layer, light absorption layer, and buffer layer;
[0097] 4.2) Use Scotch tape or Nitto tape to remove the + Mechanically peel off the chalcogenide single crystal to form a chalcogenide two-dimensional material, then use PDMS, PC or PI with a weak adhesive organic substrate to stick multiple two-dimensional materials from the tape, and select the two-dimensional material of appropriate size and thickness under a microscope, and then transfer it to the surface of the dielectric layer as a charge layer through dry transfer technology, ensuring that it does not contact the lower electrode;
[0098] The two-dimensional material is peeled off from the p-type chalcogenide single crystal using the mechanical exfoliation method described above, and the appropriate two-dimensional material is transferred to the surface of the charge layer using the same dry transfer technique as the above method to serve as the multiplication layer;
[0099] The two-dimensional material is formed by mechanically exfoliating the intrinsic chalcogenide single crystal by the mechanical exfoliation method, and the appropriate two-dimensional material is transferred to the surface of the multiplication layer as the light absorption layer by using a dry transfer technology;
[0100] The two-dimensional material is formed by mechanically exfoliating the P + type chalcogenide single crystal by the mechanical exfoliation method, and the appropriate two-dimensional material is transferred to the surface of the light absorption layer as the buffer layer by using a dry transfer technology;
[0101] The horizontal projection area of the charge layer is greater than or equal to the horizontal projection area of the multiplication layer, which is greater than or equal to the horizontal projection area of the light absorption layer, which is greater than or equal to the horizontal projection area of the buffer layer, and the adjacent two layers are combined with each other and do not fall off;
[0102] 5) Preparation of the upper electrode
[0103] 5.1) Preparation of the patterned electrode;
[0104] 5.2) The upper electrode prepared in step 5.1) is transferred to the upper surface of the buffer layer of the semiconductor stack structure as the upper electrode;
[0105] 6) Post-processing
[0106] The device obtained in step 5) is annealed in an inert atmosphere, and annealed at 100-300°C for 0.5-5h to obtain a chalcogenide avalanche photodetector.
[0107] Example 1:
[0108] A high-gain InSe avalanche detector and a preparation method thereof, the device structure of which comprises, from bottom to top, a Si substrate, a SiO2 film (dielectric layer), a Cr / Au lower electrode, an N + type semiconductor InSe:Sn with a carrier concentration of 5×10 17 cm -3 (Charge layer), a P 17 type semiconductor InSe:Mn with a carrier concentration of 2×10 16 cm -3 (Multiplication layer), an intrinsic InSe with a carrier concentration of 1×10 + cm 0.9 (P 0.1 type semiconductor InSe 17 cm -3 (Buffer layer), and a Cr / Au upper electrode.
[0109] The structure is as shown in Figure 1 and Figure 2 , and the specific preparation steps are as follows:
[0110] 1) The Si substrate for the high-gain InSe avalanche detector is a low-resistance Si substrate with a resistivity of 0.001-0.005 Ω·cm and a thickness of 500 μm. It is soaked in aqua regia for 120 minutes, rinsed with deionized water, and then ultrasonically cleaned in isopropyl alcohol, acetone, ethanol, and deionized water, followed by drying with nitrogen. A 285 nm thick SiO2 dielectric layer is deposited on the Si substrate.
[0111] 2) A photoresist was applied to a clean Si / SiO2 surface, a mask was applied, and the photoresist was cured by UV exposure. Uncured photoresist was then removed in a developer. The substrate was then placed in a magnetron sputtering vacuum chamber under vacuum conditions of 4E-4 Pa (10 / 50 nm) and a power of 50 W to deposit a Cr / Au bottom electrode on the SiO2 / Si surface. The substrate was then placed in an acetone solution to remove the photoresist from the Si / SiO2 surface.
[0112] 3) Using mechanical stripping method, Scotch tape is used to strip the doped or alloyed bulk material to obtain a two-dimensional material with uniform thickness. Combined with dry transfer technology, the grown Sn-doped N + Type InSe is transferred to the Si / SiO2 surface and does not form contact with the lower electrode, with a thickness of 30nm.
[0113] Using the same mechanical stripping and dry transfer method, Mn-doped P-type InSe with a similar area to InSe:Sn was selected and transferred to the InSe:Sn surface with a thickness of 50 nm as a multiplication layer.
[0114] Using the same mechanical exfoliation and dry transfer method, an intrinsic InSe flake with the same or similar area as the P-type InSe and a thickness of about 20nm was selected and transferred to the P-type InSe:Mn surface with a thickness of 80nm. This layer served as the light absorption layer.
[0115] Then, the mechanical exfoliation method was used to remove the InSe 0.9 Te 0.1 Alloyed P + The InSe material is peeled off and transferred to the light absorption layer, serving as a transport channel for carriers and forming an ohmic contact with the upper electrode. This layer has a small surface area and a thickness of about 50nm.
[0116] 4) The patterned Au electrode with a thickness of 50 nm was prepared by electron beam evaporation. Two metal electrodes with complete shape and uniform thickness were selected as the upper electrode and transferred to the P + TypeInSe 0.9 Te 0.1 On the upper surface of the material, two Au electrodes are placed on the InSe 0.9 Te0.1 The material is on both sides, but does not produce contact between each other.
[0117] 5) Put the prepared avalanche photodetector into a single-temperature zone tube furnace, vacuumize to ~10 -4 Pa, fill the furnace with Ar2 / H2 at a flow rate of 50 sccm using a gas flow meter, and anneal the device in an Ar2 / H2 mixed atmosphere at 150°C for 30 min to improve the contact properties of the device.
[0118] 6) Use a photoelectric test system to test the photoelectric current and light response time of the InSe avalanche detector under different light powers. The photoresponsivity is 74.6 mA / W, and the response time is 0.078 s and 0.039 s.
[0119] Comparative Example 1:
[0120] An InSe photodetector with an M-S-M (metal-semiconductor-metal) structure and a preparation method thereof. The device is an InSe photodetector with a symmetric electrode structure, and the structure includes a Si substrate, a SiO2 dielectric layer, symmetric metal electrodes, and an intrinsic InSe carrier concentration of 1×10 16 cm -3 as a light absorption layer.
[0121] The specific preparation steps are as follows:
[0122] 1) Based on low-resistance Si with a resistivity of 0.001-0.005 Ω·cm and a thickness of 500 μm. A SiO2 layer with a thickness of 285 nm is prepared on the Si substrate as a dielectric layer. It is soaked in aqua regia for 120 min, washed with deionized water, then ultrasonically cleaned in isopropyl alcohol, acetone, ethanol, and deionized water in turn, and dried with nitrogen.
[0123] 2) Apply photoresist to the clean Si / SiO2 surface and paste a mask, expose the photoresist to ultraviolet light to solidify it, and remove the unhardened photoresist in the developer. The patterned electrode area is exposed, and it is placed in a magnetron sputtering vacuum chamber under a vacuum of 4E-4 Pa, with a power of 50 W, to deposit a Cr / Au electrode on the Si / SiO2 surface with a thickness of 10 / 50 nm. Then it is placed in an acetone solution to remove the residual photoresist on the SiO2 surface.
[0124] 3) Use Scotch tape to mechanically exfoliate the undoped intrinsic InSe bulk material to obtain a uniform thickness of two-dimensional material. Combine the dry transfer technology, select an intrinsic InSe with a thickness of about 20 nm under a microscope, and transfer the InSe to the SiO2 surface. The two sides of the InSe are lapped on the Cr / Au electrodes, and the intrinsic InSe serves as a light absorption layer.
[0125] 4) Put the prepared symmetric structure M-S-M photodetector into a single-temperature zone tube furnace, vacuumize to ~ 10 - 4 Pa, fill the furnace with Ar2 / H2 at a flow rate of 50 sccm using a gas flow meter, and anneal the device in an Ar2 / H2 mixed atmosphere at 150℃ for 30 min to improve the contact properties of the device.
[0126] 5) Use a photoelectric test system to test the photoelectric current and photoresponse time of the InSe photodetector under different light powers. The photoresponsivity is calculated to be 84.84 mA / W, and the response time is 870.925 s and 67.560 s.
[0127] Example 2:
[0128] A high-gain InSe avalanche detector and a preparation method thereof, the device structure of which comprises, from bottom to top, a Si substrate, an Al2O3 film as a dielectric layer, a Ti / Au lower electrode with a thickness of 5 / 40 nm, an N + type semiconductor InSe:Sn as a charge layer (carrier concentration of 9×10 18 cm -3 , thickness of about 8 nm), a P type semiconductor InSe:Zn as a multiplication layer (carrier concentration of 3×10 17 cm -3 , thickness of about 10 nm), an intrinsic InSe as a light absorption layer (carrier concentration of 5×10 16 cm -3 , thickness of 30 nm), a P + type semiconductor InSe 0.9 Te 0.1 as a buffer layer (doping concentration of 8×10 18 cm -3 , thickness of about 15 nm), and an Au upper electrode with a thickness of 50 nm.
[0129] The specific preparation steps are as follows:
[0130] 1) The Si substrate based on the high-gain InSe avalanche detector is low-resistance Si with a resistivity of 0.001-0.005 Ω·cm and a thickness of 500 μm. It is immersed in aqua regia for 120 min, washed with deionized water, and then ultrasonically cleaned in isopropyl alcohol, acetone, ethanol, and deionized water in sequence, and dried with nitrogen. An Al2O3 film with a thickness of 300 nm is deposited on the Si substrate as a dielectric layer.
[0131] 2) A photoresist was applied to a clean Si / Al2O3 surface, and a mask was placed on it. The photoresist was cured by UV exposure, and the uncured photoresist was removed in a developer. The substrate was then placed in a magnetron sputtering vacuum chamber. Under vacuum conditions of 4E-4 Pa, Ti and Au electrodes were sputtered at a power of 50 W to a thickness of 5 nm and 40 nm, respectively. The substrate was then placed in an acetone solution to remove the photoresist from the Si / Al2O3 surface.
[0132] 3) Mechanical stripping method is used to use Scotch tape to peel off the doped or alloyed bulk material to obtain a two-dimensional material with uniform thickness. Combined with dry transfer technology, the grown Sn-doped N + The type InSe is transferred to the unetched Si / Al2O3 surface and does not form contact with the lower electrode with a thickness of 8nm.
[0133] Using the same mechanical stripping and dry transfer method, Zn-doped P-type InSe with a similar area to InSe:Sn was selected and transferred to the InSe:Sn surface with a thickness of 10 nm.
[0134] Using the same mechanical exfoliation and dry transfer method, an intrinsic InSe flake with the same or similar area as the P-type InSe was selected and transferred to the P-type InSe:Zn surface with a thickness of 20 nm. This layer served as the light absorption layer.
[0135] Then, the mechanical exfoliation method was used to remove the InSe 0.9 Te 0.1 Alloyed P + The InSe bulk material is peeled off and transferred to the light absorption layer, serving as a carrier transport channel and forming an ohmic contact with the upper electrode. This layer has a small surface area and a thickness of about 15nm.
[0136] 4) The patterned Au electrode with a thickness of 50 nm was prepared by electron beam evaporation. Two metal electrodes with complete shape and uniform thickness were selected as the upper electrode and transferred to the P + TypeInSe 0.9 Te 0.1 On the upper surface of the material, two Au electrodes are placed on the InSe 0.9 Te 0.1 Both sides of the material, but not in contact with each other.
[0137] 5) Place the prepared avalanche photodetector into a single-temperature zone tube furnace, evacuate to 5E-4Pa, use a gas flow meter to fill the furnace with Ar2 / H2 at a flow rate of 50sccm, and anneal the device in an Ar2 / H2 mixed atmosphere at 200°C for 30 minutes to improve the contact characteristics of the device.
[0138] 6) The photoelectric test system is used to test the photoelectric current and the light response time of the InSe avalanche detector under different light powers. The light responsivity is calculated to be 55.4 mA / W, and the response time is 0.086 s and 0.153 s.
[0139] Comparative Example 2 (lacking a buffer layer):
[0140] The detector structure of this example includes, from bottom to top, a Si substrate, an Al2O3 film as a dielectric layer, a Ti / Au lower electrode with a thickness of 5 / 40 nm, an N + type semiconductor InSe:Sn as a charge layer (carrier concentration of 9 x 10 18 cm -3 , thickness of about 8 nm), a P type semiconductor InSe:Zn as a multiplication layer (carrier concentration of 3 x 10 17 cm -3 , thickness of about 10 nm), an intrinsic InSe as a light absorption layer (carrier concentration of 5 x 10 16 cm -3 , thickness of 30 nm), and an Au upper electrode with a thickness of 50 nm.
[0141] The specific preparation steps are as follows:
[0142] 1) The Si substrate of the photoelectric detector is a low-resistance Si with a resistivity of 0.001-0.005 Ω·cm and a thickness of 500 μm. It is immersed in aqua regia for 120 min, washed with deionized water, and then ultrasonically cleaned in isopropyl alcohol, acetone, ethanol, and deionized water in sequence, and dried with nitrogen. An Al2O3 film with a thickness of 300 nm is deposited on the Si substrate as a dielectric layer.
[0143] 2) The photoresist is coated on the clean Si / Al2O3 surface, and the mask plate is pasted. The photoresist is cured by ultraviolet exposure, and the uncured photoresist is removed in the developing solution. It is placed in a magnetron sputtering vacuum chamber under vacuum conditions with a vacuum degree of 4E-4 pa, and Ti and Au electrodes are sputtered at a power of 50 W, with a thickness of 5 / 40 nm. Then it is placed in an acetone solution to remove the photoresist on the Si / Al2O3 surface.
[0144] 3) The mechanical exfoliation method is used to exfoliate the two-dimensional material with uniform thickness from the doped or alloyed bulk material using Scotch tape. Combined with the dry transfer technology, the grown Sn-doped N + type InSe is transferred to the unetched Si / Al2O3 surface under a microscope, and does not form contact with the lower electrode, with a thickness of 8 nm.
[0145] The same mechanical peeling and dry transfer method was used to select P-type InSe doped with Zn with an area similar to that of InSe:Sn and transfer it to the surface of InSe:Sn with a thickness of 10 nm.
[0146] The same mechanical peeling and dry transfer method was used to select an intrinsic InSe flake with an area similar to or the same as that of P-type InSe:Zn and transfer it to the surface of P-type InSe:Zn with a thickness of 20 nm, which served as a light absorption layer.
[0147] 4) A patterned Au electrode was prepared by electron beam evaporation with a thickness of 50 nm. Two metal electrodes with complete shapes and uniform thicknesses were selected as upper electrodes and transferred to the upper surface of the intrinsic InSe material by dry transfer technology, i.e., the upper electrodes directly contacted the light absorption layer. The two Au upper electrodes were placed on both sides of the light absorption layer material, but did not contact each other.
[0148] 5) The prepared photodetector was placed in a single-temperature-zone tube furnace, vacuumed to 5E-4 Pa, and filled with Ar2 / H2 at a flow rate of 50 sccm using a gas flow meter. The device was annealed in an Ar2 / H2 mixed atmosphere at 200°C for 30 min to improve the contact properties of the device.
[0149] 6) The photoelectric test system was used to test the photocurrent and light response time of the InSe photodetector under different light powers. The light responsivity was calculated to be 42.1 mA / W, and the response times were 6.1 s and 5.3 s.
[0150] Example 3:
[0151] A high-gain InSe avalanche photodetector and a preparation method thereof, the device structure of which comprises, from bottom to top, a Si substrate, a HfO2 thin film as a dielectric layer, a Ti / Au lower electrode with a thickness of 5 / 40 nm, an N + type semiconductor InSe:Ge as a charge layer (carrier concentration of 7×10 18 cm -3 , thickness of about 15 nm), a P-type semiconductor InSe:Zn as a multiplication layer (carrier concentration of 5×10 17 cm -3 , thickness of about 20 nm), an intrinsic InSe as a light absorption layer (carrier concentration of 1×10 17 cm -3 , thickness of 30 nm), a P + type semiconductor In 0.9 Ga 0.1 Se as a buffer layer (carrier concentration of 5×10 18 cm -3 , thickness of about 25 nm), and an Au upper electrode with a thickness of 50 nm.
[0152] The specific preparation steps are as follows:
[0153] 1) The Si substrate for the high-gain InSe avalanche detector is low-resistance Si with a resistivity of 0.001-0.005 Ω·cm and a thickness of 500 μm. It is immersed in aqua regia for 120 min, washed with deionized water, then ultrasonically cleaned in isopropyl alcohol, acetone, ethanol and deionized water in sequence, and dried with nitrogen. A 300 nm-thick HfO2 layer is deposited on the Si substrate as a dielectric layer.
[0154] 2) The clean Si / HfO2 surface is coated with photoresist, and a mask plate is pasted. Ultraviolet exposure solidifies the photoresist, and the un-solidified photoresist is removed in a developing solution. It is placed in a magnetron sputtering vacuum chamber, and a Ti / Au electrode is sputtered at a power of 50 W under vacuum conditions at a vacuum degree of 4E-4 Pa. Subsequently, it is placed in an acetone solution to remove the photoresist on the Si / HfO2 surface.
[0155] 3) The mechanical exfoliation method is used to exfoliate the doped or alloyed bulk material with a uniform thickness of two-dimensional material using a Think Silicon tape. In combination with the dry transfer technique, the grown Ge-doped N + type InSe is transferred to the un-etched Si / HfO2 surface without forming contact with the lower electrode, and the thickness is 15 nm.
[0156] The same mechanical exfoliation and dry transfer method is used to select Zn-doped P-type InSe with an area similar to that of InSe:Sn, which is transferred to the InSe:Sn surface as a multiplication layer, and the thickness is 20 nm.
[0157] The same mechanical exfoliation and dry transfer method is used to select an intrinsic InSe flake with an area similar to that of P-type InSe, which is transferred to the P-type InSe:Zn surface as a light absorption layer, and the thickness is 30 nm.
[0158] Subsequently, the above-mentioned mechanical exfoliation method is used to exfoliate In 0.9 Ga 0.1 Se alloyed P + type InSe bulk material, which is transferred to the light absorption layer as a carrier transport channel and forms ohmic contact with the upper electrode, and the layer has a small surface area and a thickness of about 25 nm.
[0159] 4) The patterned Au electrode is prepared by the electron beam evaporation method, and the thickness is 50 nm. Two metal electrodes with complete shape and uniform thickness are selected as the upper electrode, which is transferred to the P + type In 0.9 Ga 0.1The upper surface of the Se material, two Au electrodes are placed on the In 0.9 Ga 0.1 Se material on both sides, but not in contact with each other.
[0160] 5) Put the prepared avalanche photodetector into a single-temperature zone tube furnace, vacuumize to ~ 10 -4 Pa, use a gas flow meter to fill the furnace with Ar2 / H2 at a flow rate of 50 sccm, so that the device is in an Ar2 / H2 mixed atmosphere, and annealed at 100℃ for 60min to improve the contact properties of the device.
[0161] 6) Use a photoelectric test system to test the photoelectric current and light response time of the InSe avalanche detector under different light powers. The photoresponsivity is calculated to be 36.4mA / W, and the response time is 0.085s and 0.078s.
[0162] Example 4:
[0163] The difference from Example 3 is that the area of the light absorption layer is 50% of the multiplication layer area; that is
[0164] In step 3), the same mechanical peeling and dry transfer method is used to select an intrinsic InSe flake with an area of about 50% of the P-type InSe area, and transfer it to the surface of the P-type InSe:Zn.
[0165] Use a photoelectric test system to test the photoelectric current and light response time of the InSe avalanche detector under different light powers. The photoresponsivity is calculated to be 29.4mA / W, and the response time is 0.097s and 0.12s.
[0166] Comparative Example 3 (lacking an annealing process)
[0167] The photoelectric detector structure from bottom to top includes a Si substrate, a HfO2 film as a dielectric layer, a Ti / Au lower electrode with a thickness of 5 / 40nm, an N + type semiconductor InSe:Ge as a charge layer (carrier concentration of 7×10 18 cm -3 , thickness of about 15nm), P-type semiconductor InSe:Zn as a multiplication layer (carrier concentration of 5×10 17 cm -3 , thickness of about 20nm), intrinsic InSe as a light absorption layer (carrier concentration of 1×10 17 cm -3 , thickness of 30nm), P + semiconductor In 0.9 Ga 0.1 Se as a buffer layer (carrier concentration of 5×10 18 cm-3 Au electrode thickness is 50 nm.
[0168] The specific preparation steps are as follows:
[0169] 1) The Si substrate based on high-gain InSe avalanche detector is low-resistance Si with a resistivity of 0.001-0.005 Ω·cm and a thickness of 500 μm. It is immersed in aqua regia for 120 min, washed with deionized water, then ultrasonically cleaned in isopropyl alcohol, acetone, ethanol and deionized water in sequence, and dried with nitrogen. A HfO2 layer with a thickness of 300 nm is deposited on the Si substrate as a dielectric layer.
[0170] 2) The clean Si / HfO2 surface is coated with photoresist, and a mask plate is pasted. Ultraviolet exposure solidifies the photoresist, and the un-solidified photoresist is removed in the developing solution. It is placed in a magnetron sputtering vacuum chamber under vacuum conditions with a vacuum degree of 4E-4 pa, and a Ti / Au electrode is sputtered at a power of 50 W, with a thickness of 5 / 40 nm. Then it is placed in an acetone solution to remove the photoresist on the Si / HfO2 surface.
[0171] 3) The mechanical exfoliation method is used to exfoliate the doped or alloyed bulk material with a uniform thickness of two-dimensional material using a think tape. Combined with the dry transfer technology, the grown Ge-doped N + type InSe is transferred to the unetched Si / HfO2 surface without forming contact with the lower electrode, with a thickness of 15 nm.
[0172] The same mechanical exfoliation and dry transfer method is used to transfer Zn-doped P-type InSe with an area similar to that of InSe:Sn to the InSe:Sn surface, with a thickness of 20 nm.
[0173] The same mechanical exfoliation and dry transfer method is used to transfer an intrinsic InSe flake with an area of about 50% of the area of P-type InSe to the P-type InSe:Zn surface, with a thickness of 30 nm, which serves as a light absorption layer.
[0174] Then, the above-mentioned mechanical exfoliation method is used to exfoliate the alloyed P 0.9 Ga 0.1 Se from the P + type InSe bulk material and transfer it to the absorption layer as a carrier transport channel and form ohmic contact with the upper electrode. This layer has a small surface area and a thickness of about 25 nm.
[0175] 4) The patterned Au electrode is prepared by electron beam evaporation, with a thickness of 50 nm. Two metal electrodes with complete shape and uniform thickness are selected as the upper electrode, which is transferred to the P +Type In 0.9 Ga 0.1 On the upper surface of Se material, two Au electrodes are placed on In 0.9 Ga 0.1 Se materials on both sides, but not in contact with each other.
[0176] 5) Using a photoelectric testing system, the photocurrent and photoresponse time of the InSe avalanche detector were measured at different optical powers. The calculated photoresponsivity was 27.7 mA / W, and the response time was 6.8 s and 5.5 s.
[0177] Through the above-mentioned embodiments and comparative examples, it can be seen that the embodiments 1-4 using the method of the present invention illustrate that the avalanche photodetector structure and preparation method proposed by the present invention have significant advantages in improving the comprehensive performance of the device. In the embodiment, by optimizing the doping concentration and thickness control of each functional layer, on the basis of ensuring high light responsivity, the dark current and carrier recombination are effectively suppressed, and the carrier transport capacity is improved. The photoresponsivity and response time of the detector finally prepared are significantly better than those of the comparative example under the same conditions (whether it is a structural difference or a preparation process difference). Therefore, it can be further proved that the structural design and preparation method provided by the present invention can achieve the simultaneous optimization of photoresponsivity and response speed without the need for complex processes, overcome the performance trade-off problem existing in traditional photodetectors, have high controllability and structural versatility, and have broad application prospects in the field of high-speed, high-sensitivity detection (such as low-light intensity imaging, biosensing and environmental monitoring, etc.). In addition to the chalcogenide compound indium selenide, the present invention also uses molybdenum sulfide and gallium selenide to carry out the same embodiment within the aforementioned process conditions. Through the test of the comprehensive performance of the final device, it is found that the same effect as indium selenide can be produced, and both the light responsivity and the response speed can be improved.
[0178] The above description is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with this technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present invention, and these modifications or replacements should all be included in the scope of protection of the present invention.
Claims
1. A high-gain chalcogenide avalanche photodetector, characterized in that: An avalanche photodetector with a surface-incident structure, comprising a substrate, a dielectric layer, a semiconductor stacked structure, a lower electrode, and an upper electrode; The dielectric layer is located on the upper surface of the substrate; The semiconductor stacked structure is located on the upper surface of the dielectric layer and comprises, from bottom to top, a charge layer, a multiplication layer, a light absorption layer, and a buffer layer; wherein the charge layer and the multiplication layer together constitute an avalanche multiplication region; The charge layer is N + The multiplication layer is a P-type doped or alloyed chalcogenide two-dimensional material; the light absorption layer is an intrinsic chalcogenide two-dimensional material; the buffer layer is a P-type doped or alloyed chalcogenide two-dimensional material. + The two adjacent layers form van der Waals contact through van der Waals force, and the two layers adhere to each other without falling off; and the horizontal projection area of the charge layer is greater than or equal to the horizontal projection area of the multiplication layer, greater than or equal to the horizontal projection area of the light absorption layer, and greater than or equal to the horizontal projection area of the buffer layer; the thickness of the charge layer is less than the thickness of the multiplication layer and less than the thickness of the light absorption layer; The electron concentration of the charge layer is 5×10 17 -9×10 18 cm -3 The hole concentration in the multiplication layer is 2×10 17 -5×10 18 cm -3 ; The carrier concentration of the light absorbing layer is 1×10 16 -5×10 17 cm -3 The hole concentration of the buffer layer is 5×10 17 -9×10 18 cm -3 ; The lower electrode does not contact the semiconductor stacked structure and is located on the upper surface of the dielectric layer; The upper electrode is located on the upper surface of the buffer layer and forms an ohmic contact with the buffer layer.
2. The high-gain chalcogenide avalanche photodetector according to claim 1, characterized in that: The thickness of the charge layer is 5-50 nm; The thickness of the multiplication layer is 5-80 nm; The thickness of the light absorbing layer is 10-200 nm; The thickness of the buffer layer is 10-100 nm.
3. The high-gain chalcogenide avalanche photodetector according to claim 1 or 2, characterized in that: The doping elements in the charge layer are one or more of Ge, Sn, Pb, Cl, Br and I; alloyed to form one or more of InGaSe, InSeTe and InSeS; The doping elements in the multiplication layer are one or more of Mn, V, Zn, Cd, Hg, Sb, Al, As and Bi, which are alloyed to form one or more of InGaSe, InSeTe and InSeS; The doping elements in the buffer layer are one or more of Mn, V, Zn, Cd, Hg, Sb, Al, As and Bi, which are alloyed into one or more of InGaSe, InSeTe and InSeS.
4. The high-gain chalcogenide avalanche photodetector according to claim 3, characterized in that: The lower electrode includes a first electrode and a second electrode, which are respectively located on both sides of the upper surface of the dielectric layer, and the material is one or more combinations of Cr, Ti, Ag, Au, Pt, Al, In, Pa, W, graphite, ITO, FTO, and AZO, and the thickness is 10-80 nm; The upper electrode includes a third electrode and a fourth electrode, which are respectively located on the upper surface of the buffer layer. The two electrodes are not in contact with each other. The material is one or more combinations of Cr, Ti, Ag, Au, Pt, Al, In, Pa, W, graphite, ITO, FTO, and AZO, and the thickness is 10-80 nm.
5. The high-gain chalcogenide avalanche photodetector according to claim 4, characterized in that: The material of the substrate is one of Si, sapphire, mica, PET, PC and PDMS; The material of the dielectric layer is one or more of SiO2, HfO2, Al2O3, hBN, and PDMS.
6. The high-gain chalcogenide avalanche photodetector according to claim 1, characterized in that: The chalcogenide compound is InSe.
7. The method for preparing the high-gain chalcogenide avalanche photodetector according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Processing substrate Treating the substrate to remove impurities on the substrate surface; 2) Preparation of dielectric layer Preparing a dielectric layer on the surface of the substrate treated in step 1); 3) Preparation of lower electrode A patterned electrode structure is photolithographically formed on the dielectric layer, and then an electrode having a thickness that meets the requirements is deposited on the electrode structure as a lower electrode; or, Directly transfer a pre-patterned electrode with a thickness that meets the requirements to the surface of the dielectric layer as a lower electrode; 4) Preparation of semiconductor stacked structures 4.1) Using a melt process to prepare doped or alloyed chalcogenide materials with the required conductivity type and carrier concentration for the charge layer, multiplication layer, light absorption layer, and buffer layer; 4.2) Mechanically exfoliating the chalcogenide material obtained in step 4.1) into a two-dimensional material having a desired thickness, in the order of charge layer, multiplication layer, light absorption layer, and buffer layer from bottom to top, and transferring the material to the target location using a dry transfer technique, ultimately forming a semiconductor stacked structure in which adjacent layers are bonded to each other and do not fall off; 5) Preparation of upper electrode 5.1) Preparing patterned electrodes; 5.2) transferring the upper electrode prepared in step 5.1) to the upper surface of the buffer layer of the semiconductor stack structure as the upper electrode; 6) Post-processing The device obtained in step 5) is annealed in an inert atmosphere at 100-300° C. for 0.5-5 h to obtain a chalcogenide avalanche photodetector.
8. The method for preparing a high-gain chalcogenide avalanche photodetector according to claim 7, characterized in that: Step 1) is specifically as follows: The substrate was immersed in piranha solution or aqua regia, first cleaned with deionized water, then cleaned in isopropyl alcohol, acetone and ethanol in sequence, and finally ultrasonically cleaned in deionized water, and the substrate was blown dry with nitrogen.
9. The method for preparing a high-gain chalcogenide avalanche photodetector according to claim 8, characterized in that: Step 4.2) is specifically as follows: Use Scotch tape or Nitto tape from N + Mechanically peel off the chalcogenide single crystal to form a chalcogenide two-dimensional material, then use PDMS, PC or PI with a weak adhesive organic substrate to stick multiple two-dimensional materials from the tape, and select the two-dimensional material of appropriate size and thickness under a microscope, and then transfer it to the surface of the dielectric layer as a charge layer through dry transfer technology, ensuring that it does not contact the lower electrode; The two-dimensional material is peeled off from the p-type chalcogenide single crystal using the mechanical exfoliation method described above, and the appropriate two-dimensional material is transferred to the surface of the charge layer using the same dry transfer technique as the above method to serve as the multiplication layer; The two-dimensional material is formed by mechanically exfoliating the intrinsic chalcogenide single crystal using the above-mentioned mechanical exfoliation method, and the appropriate two-dimensional material is transferred to the surface of the multiplication layer using a dry transfer technique to serve as a light absorption layer; The mechanical stripping method described above was used to remove the + A two-dimensional material is formed by mechanical exfoliation on a single crystal of a type chalcogenide compound, and a suitable two-dimensional material is transferred to the surface of the light absorption layer using a dry transfer technique as a buffer layer; The horizontal projection area of the charge layer is greater than or equal to the horizontal projection area of the multiplication layer, and is greater than or equal to the horizontal projection area of the light absorption layer and is greater than or equal to the horizontal projection area of the buffer layer.
10. The method for preparing a high-gain InSe avalanche photodetector according to claim 9, characterized in that: In step 6), the inert atmosphere is Ar2 or a mixture of Ar2 / H2; The annealing temperature is 150°C and the time is 0.5h.